2022
DOI: 10.7717/peerj.14554
|View full text |Cite
|
Sign up to set email alerts
|

The biomarkers discovery of hyperuricemia and gout: proteomics and metabolomics

Abstract: Background Hyperuricemia and gout are a group of disorders of purine metabolism. In recent years, the incidence of hyperuricemia and gout has been increasing, which is a severe threat to people’s health. Several studies on hyperuricemia and gout in proteomics and metabolomics have been conducted recently. Some literature has identified biomarkers that distinguish asymptomatic hyperuricemia from acute gout or remission of gout. We summarize the physiological processes in which these biomarkers ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 116 publications
2
3
0
Order By: Relevance
“…Zhao Q et al demonstrated a nonlinear relationship between serum UA and TyG index in children with short stature, which remained nonlinear after gender stratification [ 41 ]. Hyperuricemia is an important influence in causing gout [ 42 ], thus supporting our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Zhao Q et al demonstrated a nonlinear relationship between serum UA and TyG index in children with short stature, which remained nonlinear after gender stratification [ 41 ]. Hyperuricemia is an important influence in causing gout [ 42 ], thus supporting our findings.…”
Section: Discussionsupporting
confidence: 90%
“…We are not aware of any untargeted metabolomics studies investigating risk factors of gout. Nevertheless, previous research on prevalent gout has established connections with altered amino acid levels, perturbations in purine, glycerophospholipid, sphingolipid, and carbohydrate metabolism [35]. These ndings were also partially replicated in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Studies have conrmed that glycerophospholipid metabolism, arachidonic acid metabolism and alanine, aspartate and glutamate metabolism may be related to the pathogenesis of hyperuricemia and gout. 10 In the pathway of glycerophospholipid metabolism, the levels of glycerylphosphorylcholine, glycerol 3-phosphate and LysoPC(20:1(11Z)/0:0) in MD group were signicantly increased, while the level of PE(16:0/20:3(5Z,8Z,11Z)) was decreased. Aer the treatment of MNH, the levels of glycerylphosphorylcholine, glycerol 3-phosphate, LysoPC(20:1(11Z)/0:0) and PE(16:0/ 20:3(5Z,8Z,11Z)) were signicantly adjusted.…”
Section: Mnh Administration Changed Serum Proling In Hua Micementioning
confidence: 94%
“…With its comprehensive and dynamic properties, metabolomics has exhibited significant advantages in the entire understanding of the efficacy mechanism of drug. 10 The gut microbiota plays an important role in cultivating host immunity, digesting food, regulating intestinal endocrine function and nerve signals, altering drug action and metabolism, removing toxins, and producing a variety of compounds that affect the host. 11 Furthermore, an increasing number of studies have combined 16S rRNA amplicon sequencing and metabolomic methods to investigate the relationship between gut microbiota and circulating metabolites.…”
Section: Introductionmentioning
confidence: 99%